THE EFFECT OF FIDDLEHEADS(Diplazium esculentum) EXTRACTAPPLICATION TO THE QUALITY OF FRESH CATFISH (Pangasius hypophthalmus) - Noprianto Noprianto; Edison Edison; N Ira Sari (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2018)
AbstractTheobjective of the research was to determine the effect of fiddleheads extract application to the quality of fresh catfish (Pangasius hypohtalmus). The benefit of this research was to make fiddleheads extract as a liquid for one of natural preservatives alternative which kept in room temperature. The experimental method was used in this research with soaking of fresh catfish with different fiddleheads liquid extract. The Design used was Group Randomized Design with 3 treatments i.e.without fiddleheads extract (P0), 50 ml of fiddleheads extract (P1), 75 ml of fiddleheads extract (P2). While as a group /repetition waslong observation 0, 4, 8, and 12 hours. Tested parameters were organoleptic, pH, Total Volatile Base (TVB) and Total Plate Count (TPC). The results showed that the different of fiddleheads extract application to the quality of fresh catfish had effects towards appearance, aroma, texture, flavor, pH, TPC, and TVB value. The soakingwith 75 ml of fiddleheads extract shown the highest organoleptic value, whereas forpH, TVB and TPCwas the lowest value for 12 observation time. The characteristics of treatment with soaking 75 ml of fiddleheads extract were eyes (6.28) with intact characteristic, no defects, the colour was less brilliant, and tight skin; gills (6.12) neutral specific aroma;innards value (5.88) compact; meat value (5.88) less dense and less elastic; aroma value (6.12) with the specific aroma of fresh and slightly fishy fish;pH 6.3;TVB 17.50 mgN/100 gram and TPC 3.8 x 105 Cfu/gram..Keywords: fiddleheads extract, fresh catfish, organoleptic